Finite-element human body model for automotive safety: From a kinematic model towards an injury model - Baudrit, Pascal; Song, Eric (European Journal of Computational Mechanics, 2005)
This article presents a finite element human body model, used in the Laboratoire d’Accidentologie, de Biomécanique et d’études du comportement humain of French car manufacturers for its occupant safety research programs. The working-out, the main construction steps of and the validation process are described. An example of application, which consists of a comparative study in frontal crash with a dummy model, illustrates the interest and limitations, through the most significant results. After a basic study, applied to the development of a new thoracic criterion highlighting real safety, the approach to improve the model into a 3D breakable model is shown. The bone condition differences are taken into account. Several future research prospects are exhibited in order to reinforce the human body model.